The Correlation of Nutrition Knowledge, Diet, Physical Activity and Snack Food Consumption Habits with Nutritional Status of Elementary School-age Children at SDIT Babul Jannah - Dewi, Rizka Erpina; Hekmah, Nurul; Suryani, Nany; Yudistira, Sigit (Jurnal Pangan Kesehatan dan Gizi Universitas Binawan, 2024)
Nutritional problems in school-age children can lead to physical impairment, reduced concentration while learning, and decreased intelligence which has an impact on children's school performance. Nutritional knowledge is an indirect factor in triggering under- and over-nutrition in primary school children. A child's poor diet will hamper growth and development. Low physical activity and consuming excess snacks will lead to overweight status. This study aims to determine the relationship between nutritional knowledge, diet, physical activity and snacks consumption habits with nutritional status in elementary school children at SDIT Babul Jannah. This study used quantitative methods. This type of research is observational with a cross sectional approach. Sample selection was carried out by random sampling method, the sample totaled 55 respondents. The results of the study using the Rank Spearman statistical test showed nutritional knowledge (p = 0.716), physical activity (p = 0.558) was not associated with nutritional status, while diet (p = 0.001), snacks consumption habits (p = 0.001) associated with nutritional status. It is hoped that students can increase knowledge related to nutrition, diet, physical activity and consumption habits of snacks so that in everyday life they are more selective in choosing the food consumed and do good physical activity and not excessive.